Whatsapp Group to Optimize the Mahārah Istimā’ Learning During the Covid-19 Pandemic - Aulia Mustika Ilmiani; Marsiah Marsiah; Yulia Rahmah; Mahfuz Rizqi Mubarak (Jurnal Alsinatuna, 2020)
The Covid-19 pandemic which began to plague Indonesia in March 2020 had a major impact on academic activities in higher education, including at IAIN Palangka Raya. This situation requires the lecturers to find ways to adapt to new conditions and reduce the risk of virus transmission. This study is a descriptive-qualitative research that aims to uncover the learning process of Mahārah Istimā’ using WhatsApp Group media seen from the learning objectives, materials, strategies, and evaluation. The subject of this research is lecturers of Arabic Education (PBA) at IAIN Palangka Raya who teach the Mahārah Istimā’ course. Data of the research was collected from observation, interviews, and documentation. The results showed that the learning process of Mahārah Istimā’ during the Covid-19 pandemic could run optimally in terms of the learning objectives, materials, strategies, and evaluation. The objectives of Mahārah Istimā’ learning are to understand, develop, interact, observe, conclude, and classify information. The learning materials used can be in the form of discourses, conversations, songs, guessing games, or chain messages using audio that is played through the voice note feature on the WhatsApp application. The strategies used include: (1) listen and then say, (2) listen and then answer, (3) listen and then identify, and (4) listen and then refine. The evaluations meant here involve daily evaluations for each assignment and summative evaluations, i.e. the midterm exam and the final exam.